From awareness to action: How EzyAgric's digital platform boosted farmer engagement and tackled counterfeit inputs - Ajambo, Susan; Kikulwe, Enoch; Birachi, Eliud; Ogutu, Sylvester; Stewart, Ategeka (Bioversity International and the International Center for Tropical Agriculture, 2024)
Digital platforms revolutionize agriculture by resolving supply chain inefficiencies, improving agronomic information dissemination and promoting inclusivity. They provide real-time e-extension and input availability, enabling precise decision-making and boosting productivity. Additionally, these platforms enhance transparency, traceability and profitability by directly linking farmers with input and output markets, especially in fragmented agricultural systems.